Aggregate Analysis of Packaging Machine Effectiveness Using the OEE Method at PT. XYZ - Siti Rahayu; Satria Bagus Aji; Adi Fitra; Syarah Rizkia Feriaty; Tri Ngudi Wiyatno (Universitas Islam Raden Rahmat, Malang, 2025)
In today’s competitive manufacturing industry, maintaining high production efficiency and minimizing machine downtime are critical challenges, particularly in the food sector. This study aims to analyze the effectiveness of ten CBP product packaging machines at PT. XYZ using the Overall Equipment Effectiveness (OEE) method. The research employs a quantitative approach based on primary data collected through direct observation and interviews. The OEE method measures machine performance through three indicators: Availability, Performance, and Quality. The results show that the average OEE value from October to December 2023 is 94%, exceeding the world-class standard of 85%. The dominant loss affecting effectiveness was Equipment Failure Losses (50%), followed by Rework and Defect Losses (22% each). These losses are primarily caused by machine wear, material issues, and operator handling errors. The findings indicate that the OEE method serves as an effective tool for monitoring production efficiency and planning preventive maintenance. Regular operator evaluations and standardized maintenance procedures are recommended to sustain high equipment performance levels.